Rancang Bangun Alat Pendeteksi Kecelakaan Mobil Menggunakan Sensor Akselerometer dan Sensor 801s Vibration - Adnan Mahfuzhon; Tibyani Tibyani; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The improvement of infrastructure, especially road and freeway, will make the transportation service industry more promising. One of them is car rental service business, increases up to 70%. There are several reasons why car rental service becoming the first choice than buying or owing a car, specifically for business world. Besides saving the budget, renting a motorbike also erasing several difficulties, for instances, maintenance, extension for important letters, even decreasing losing the motorbike. Based on the data obtained from the increasing of car rental service business, it is needed to keep the comfort between the service provider with the customer. The important thing to be noticed, when the service provider must maintain the rental cars. Also, the customer must take care of the rented car. From the problem, it is need to conduct a research related to accidental notification for keeping the cars and customer's comfort. The process of collecting the test data manually to be made the input for calculating naive bayes. The data adjustment is set by referring to accelerometer data, if the data is more than 4 grams so it is categorized in accident condition. Collecting the data in the running condition obtained the value of accuracy up to 90%, then when collecting in the sudden stop condition obtained up to 78%, and in accident condition obtained up to 98%. The data test results from the classification results using naive bayes, they are obtained by collecting the test data in each one for 16-time tests in every scenarios. In running condition, it is obtained the value of accuracy up to 98,7%, in the sudden stop condition obtained the value of accuracy up to 87,5% and in the accident condition obtained the value of accuracy up to 98,7%.